PERANAN MEDIA PEMBELAJARAN INTERAKTIF BERBASIS GAMIFIKASI (WORDWALL) UNTUK MENINGKATKAN HASIL BELAJAR MATA PELAJARAN ILMU PENGETAHUAN ALAM - Mulyati, Sri; US, Supardi. (TEACHER : Jurnal Inovasi Karya Ilmiah Guru, 2025)
ABSTRACT Science learning outcomes continue to face various challenges with traditional teaching methods. This study aims to examine the role of interactive learning media using Wordwall gamification in enhancing students' motivation and learning outcomes in science education. The method applied was a quasi-experimental design with pre-test and post-test involving 70 seventh-grade students, who were divided into an experimental group and a control group. Data collection was conducted through learning achievement tests, learning motivation questionnaires, and observation of activities during the learning process. The research findings indicate that the utilization of Wordwall significantly improves student learning outcomes, with the average learning achievement score for the experimental group (60.94) being higher compared to the control group (62.09). Furthermore, student learning outcomes also showed significant improvement, where the average post-test score for the experimental group (83.11) was higher than the control group (74.09). Paired sample t-test analysis indicates that the role of gamification media contributes 68% to student learning outcomes. Gamification features such as points, leaderboards, and badges in Wordwall proved effective in enhancing student engagement and active participation in science learning. This research concludes that Wordwall-based interactive learning media has a positive and significant role in improving learning motivation, which ultimately impacts student learning outcomes in science subjects. ABSTRAK Hasil pembelajaran dalam mata pelajaran IPA masih menghadapi berbagai tantangan pada metode pengajaran tradisional. Penelitian ini bertujuan untuk mengkaji peran media pembelajaran interaktif yang menggunakan gamifikasi Wordwall dalam meningkatkan motivasi dan hasil pembelajaran siswa dalam IPA. Metode yang diterapkan adalah desain quasi-experimental dengan pre-test dan post-test yang melibatkan 70 siswa kelas VII, yang dibagi ke dalam kelompok eksperimen dan kelompok kontrol. Pengumpulan data dilakukan melalui tes hasil belajar, kuesioner motivasi belajar, serta observasi aktivitas selama proses pembelajaran. Temuan penelitian menunjukkan bahwa pemanfaatan Wordwall secara signifikan meningkatkan hasil belajar siswa, dengan rata-rata skor hasil belajar untuk kelompok eksperimen (60.94) lebih tinggi dibandingkan dengan kelompok kontrol (62.09). Selain itu, hasil belajar siswa juga menunjukkan peningkatan yang signifikan, di mana nilai rata-rata post-test untuk kelompok eksperimen (83,11) lebih tinggi daripada kelompok kontrol (74.09). Analisis paired sampe t test mengindikasikan bahwa peran media gamifikasi memberikan kontribusi sebesar 68% terhadap hasil belajar siswa. Fitur-fitur gamifikasi seperti poin, papan peringkat, dan lencana dalam Wordwall terbukti efektif dalam meningkatkan keterlibatan dan partisipasi aktif siswa dalam pembelajaran IPA. Penelitian ini menyimpulkan bahwa media pembelajaran interaktif berbasis Wordwall memiliki peran yang positif dan signifikan dalam meningkatkan motivasi belajar, yang pada akhirnya berdampak pada hasil belajar siswa dalam mata pelajaran IPA.